??DETERMINATION OF MINOR AND TRACE ELEMENTS IN INDIGENOUS SULPHIDE MINERALS ? ? (Biological Sciences - PJSIR, 1999)
to develop a rather rapid, precise and sensitive method forthe determination of valuable minor and trace metals insulphide minerals using flame atomic absorption spectrophotometer.Moreover, the present studies are continuationof our earlier investigations (Siddiqi et at 1984; Naeem etat 1988; Khan et at 1990) regarding geochemical evaluationof and sphalarite of Kohistan-Hazara and the copperore deposits of North Waziristan Agency (North West FrontierProvince of Pakistan).